Sistema de gestión de talento humano y su incidencia en el desempeño laboral de los trabajadores de la florícola agrogana s.a. de la parroquia Joseguango bajo provincia de Cotopaxi en el período 2014 – 2015 - Llano Toapanta, Evelin America (2015)
The objective of the project is to improve the job performance of Floriculture AGROGANA SA workers, through the Management Talent System development, which reflects important results for them; this is dedicated to produce and market flowers in the Cotopaxi province. The main problem is the job performance deficiency, which is originate by the lack of work socialization, due to it is produced by the lack of the encouragement so the few knowledge of the professional profile is the problem too, besides the inadequate working environment is the consequences either. This study was conducted by the field research, bibliography research; hence the interview and survey which were designed have been applied. These allow us to get real information….